Transfer and analysis of Salmonella pdu genes in a range of Gram‐negative bacteria demonstrate exogenous microcompartment expression across a variety of species. Issue 1 (2nd October 2017) - Graf, Laura; Wu, Kent; Wilson, James W.
Summary: Bacterial microcompartments (MCPs) are protein organelles that typically house toxic or volatile reaction intermediates involved in metabolic pathways. Engineering bacteria to express exogenous MCPs will allow these cells to gain useful functions involving molecule compartmentalization. We cloned a 38 kb region from the Salmonella enterica serovar Typhimurium genome containing the pdu 1, 2 propanediol (1, 2 PD) utilization and cob/cbi genes using the FRT‐Capture strategy to clone and transfer large genomic segments. We transferred this clone to a range of Gram‐negative bacteria and found the clone to be functional for 1, 2 PD metabolism in a variety of species including S . Typhimurium Δ pdu, Escherichia coli, Salmonella bongori, Klebsiella pneumoniae, Cronobacter sakazakii, Serratia marcescens, and different Pseudomonas species. We successfully isolated MCPs expressed from the clone from several, but not all, of these strains, and we observed this utilizing a range of different media and in the absence of protease inhibitor. We also present a mini‐prep protocol that allows rapid, small‐scale screening of strains for MCP production. To date, this is the first analysis of cloned, exogenous microcompartment expression across several different Gram‐negative backgrounds and provides a foundation for MCP use in a variety of bacterial species using a full, intact clone. Abstract : Bacterial microcompartments (MCPs) are protein organelles that typically house toxic or volatile reaction intermediates involved in metabolic pathways. We cloned a 38 kb region from the Salmonella enterica serovar Typhimurium genome containing the pdu 1, 2 propanediol (1, 2 PD) utilization and cob/cbi genes using the FRT‐Capture strategy to clone and transfer large genomic segments. We successfully isolated MCPs expressed from the clone from several, but not all, of recipient bacteria, and we observed this utilizing a range of different media and in the absence of protease inhibitor. We also present a mini‐prep protocol that allows rapid, small‐scale screening of strains for MCP production.